Analisis Wacana Kritis dalam Cerpen Rumus Hidup Bahagia Karya Sabrina Lasama dengan Pendekatan Sara Mills - Windaryati, Woro Endah Sri; Asrofah, Asrofah (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
This article analyses Sabrina Lasama's short story Rumus Hidup Bahagia (The Formula for a Happy Life) using Sara Mills' critical discourse approach to reveal representations of women in social, cultural, and gender relations contexts. It focuses on how women are treated, viewed by men, and constructed in the narrative. The analysis shows that the main character, Anti, faces social pressure to follow the conventional formula for happiness: marry, have children, and become the wife of a well-established man. Anti is also a victim of sexual violence that is not believed, a sexual object, and a status symbol. Although they appear to be the subjects of the narrative, the women in this story are actually objects of the patriarchal social system. Anti shows resistance through manipulative actions that blur the line between obedience and resistance. This article suggests that the representation of women in literature reflects unequal power relations and can be a critique of patriarchal ideology.